PENGARUH EMISI CO₂, KONSUMSI ENERGI, DAN EKSPOR TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Yohana Feby; Putri Sari Margaret Julianty Silaban (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of CO₂ emissions, energy consumption, and exports on economic growth in Indonesia in both the short run and long run. The data used are annual time series data for the period 2004–2024 sourced from the World Bank and Our World in Data. The analytical method employed is the Error Correction Model (ECM) to capture the dynamic relationship between variables in the short run and long run. The short-run estimation results indicate that CO₂ emissions have a negative and significant effect on economic growth, while energy consumption and exports have a positive and significant effect on Indonesia's economic growth. Simultaneously, all three variables significantly affect economic growth in the short run with an R-squared value of 88.58 percent. The long-run results show that CO₂ emissions have a negative and significant effect, while energy consumption and exports have a positive and significant effect. The ECT coefficient of -1.221 confirms the existence of an error correction mechanism toward long-run equilibrium. This study concludes that controlling carbon emissions, optimizing clean energy consumption, and strengthening export competitiveness are policies that need to be integrated to promote sustainable economic growth in Indonesia.